Agama dan Modernitas dalam Praktik Ritual Mandi Safar di Kayong Utara - Wahab Wahab; Hariansyah Hariansyah; Dewi Nur Hayati (Jurnal Studi Agama dan Masyarakat, 2019)
The Sungai Jambu Malay society believes that the Safar Month brings curses and illness. Avoiding this, the local community does the Safar bath ritual by reading selected shurah in the Qur’an, performing ablution, praying safely, praying rejecting curses, blessings to the Prophet, Zikir, swearing the utterance that there is no god but Allah, helping each other, friendship, eating together, praying the intention to do  Safar bath with the aim to obtain safety and avoid curses in the month of Safar. This study uses a qualitative approach with ethnographic methods. The subject of the study is religious leaders and customary leaders. The techniques used in the study are non-participant observation, phone interviews and direct interviews.  The study revealed that the Sungai Jambu Malay society praying for the safety,  praying for longevity and rejecting disasters are a form of confidence in order that they saved from disasters and illness in the Safar month. Besides reading the surahs of al-Fatihah, al-Ikhlas, an-Naas and al-Falak to get a reward from Allah Subhanahu wa ta'ala, doing ritual bath during the safar month for the Sungai Jambu Malay society is the purification from disasters and disease. In addition, bathing also removes odors, dust, and moisturizes the skin. However, the belief of the Sungai Jambu Malay society towards the Safar month, which brought curses and illness,  there is a gap and contrary to the valid Hadith regarding the safar month.